Efektivitas Teknik Pembelajaran “SQ3R” (Survey, Question, Read, Recite and Review) untuk meningkatkan keterampilan membaca (Studi kuasi eksperimen MTsN 9 Jakarta) - Nursyamsiah Nursyamsiah; Taufik Hidayat; Azmy Ali Muchtar (Journal on Education, 2024)
Problems in Reading skill shows the lack of understanding of eighth-grade students at Government Junior Islamic School 9 in Jakarta learning the Arabic language subject about “profession”. Because of their different educational backgrounds, some of them from primary school and Islamic institute, there are It is difficult to learn the Arabic language because there are still many students who cannot read the Arabic language.This research aims: to reveal the effectiveness of learning technology “SQ3R” And to reveal the extent to which students are proficient in the reading skill of the reading aloud subject among students in the eighth grade at Government Jumior Islamic School 9 in Jakarta.This research is a quantitative research. The research method is semi-experimental. Quasi-experimental method research is research that manipulates or controls natural conditions by creating artificial conditions. The method of selecting data is observation, documents, and pre- and post-test results.Test results are used t to determine whether there were differences between the two samples of this data, an t-table It was set at 1,687 while t-score 25,267. The effectiveness of the text cooperation learning model to improve reading skill on Arabic texts in pre- and post-test data. It is known that the value of (sig) (2 Tailed( It is 0,001 > 0,005 and based on tests with one variable and one sample (Single t-test) (sig) (2 tailed) in the amount of 0,005. Therefore, the largest level is 0,000 (Significance) Smaller than 0,005, then a result from tests with one variable and one sample )Single t-test( It has great results )Significant). This score indicates that the alternative hypothesis (Ha) "Acceptable" The first hypothesis (H0) “Returned”.